2012
DOI: 10.1007/s10096-012-1647-1
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient parenteral antibiotic therapy (OPAT) at home in Attica, Greece

Abstract: Outpatient parenteral antibiotic therapy (OPAT) is considered to be a cost-effective and safe alternative treatment strategy to hospitalization. We retrospectively evaluated data regarding the demographic and treatment characteristics of patients that sought medical advice from a network of physicians performing house-call visits and who received OPAT at home during a 17-month period (May 2009 to September 2010) in Attica, Greece. A total of 91 patients (69.2 % females) received intravenous antibiotic therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Theocharis et al reported a rate of mortality of 27% and a cure rate of 72.5%, which could be due to the advanced age (85.3 ± 9 years) and comorbidities of the patients. Another study with 2 groups (above 60 years and below 60 years) performed by Cox et al reported similar rates of VAD related complications in both groups (22.4%/26.6%) and the rates of drug‐related adverse events were 22.4%/14.5%; the cure rate was 92%/94%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Theocharis et al reported a rate of mortality of 27% and a cure rate of 72.5%, which could be due to the advanced age (85.3 ± 9 years) and comorbidities of the patients. Another study with 2 groups (above 60 years and below 60 years) performed by Cox et al reported similar rates of VAD related complications in both groups (22.4%/26.6%) and the rates of drug‐related adverse events were 22.4%/14.5%; the cure rate was 92%/94%.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, more than 88% of the studies reported a cure or treatment success rate of greater than 80%. Readmission rate varied from 1% to 26%, mortality varied from 0 to 27.5% . VAD related complications ranged from 0% to 29% and adverse drug reactions rate varied from 0% to 30.2% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, OPAT has been shown to be safe and effective for a wide range of infectious diseases (ID), including skin and soft tissue infections (cellulitis, osteomyelitis, and septic arthritis), bacteremia, endocarditis, pyelonephritis, meningitis, brain abscess, and intraabdominal infections. [1][2][3][4][5][6][7][8][9][10][11] In 2004, the Infectious Diseases Society of America (IDSA) published guidelines outlining the safe and effective practice of OPAT, with specific recommendations addressing (1) appropriate patient evaluation and selection, (2) essential elements of an OPAT program, (3) roles and responsibilities of individual OPAT team members, (4) appropriate selection and administration of antibiotics for OPAT, and (5) laboratory monitoring parameters and recommended frequencies according to the antimicrobial agent used. 1 The IDSA guideline recommendations on appropriate patient and antibiotic selection for OPAT support current antimicrobial stewardship efforts directed at ensuring judicious and cost-effective use of antimicrobial agents.…”
mentioning
confidence: 99%
“…1,5 Common models for the delivery of OPAT include the infusion center model, the selfadministration model, and the long-term care facility model. 1,4,6,9,11,12 In the infusion center model, OPAT is administered in a variety of settings (e.g., hospital clinic, emergency department, urgent care center, physician's office, freestanding infusion facility). The primary limitation of this model is the need for frequent patient transportation to receive OPAT.…”
mentioning
confidence: 99%